Topical Issues Surrounding Supply Chain Management In Developing Food Industry: Kazakhstan Case Study - Sholpan I.Karkinbayeva; Kasiya A.Kirdasinova; Elmira M.Adiyetova; Ainur Zh.Kanatova; Bibinur B.Korgan (International Journal of Supply Chain Management, 2019)
In modern conditions of socioeconomic development of the Republic of Kazakhstan, one of the priority areas associated with food industry development is the development of methods for managing supply chains. The food industry development itself is crucial in current setting because the level of competitiveness of domestic food products depends on food production in the global economy. Considering the fact that traditional food logistics is no longer able to meet market requirements, it becomes increasingly important to create an innovation-driven system for tracking the supply of agri-food products. This article provides a literature review of domestic and foreign authors who conducted research on the practice of supply chain management aimed at the development of the food industry. The economic assessment of the current state of the food industry of the Republic of Kazakhstan for the implementation of the tasks of the national economy. As a result of the research, the theoretical and practical aspects of the food industry research are systematized, on the basis of which the relevant conclusions are drawn. This article puts forward various hypotheses and uses theoretical approaches, within which we can expect to stimulate sustainability of supply chain management. These approaches are presented within the framework of the following theories: institutional theory, dynamic capability theory, and the theory of stakeholders. Additionally, a conceptual framework was built on the stakeholder theory to identify indicators, drivers and barriers and achieve sustainability in the food supply chain.